Investigation of Sleep Patterns in the UG Foreign Students Regarding to Stressogenic Factors and Depression (Pilot Study - Ckhalil, Fatima El; Qiria, A.; Lomidze, N.; Gogichadze, M. (Caucasus Journal of Health Sciences and Public Health, 2020)
One third of the population in developed countries suffers from sleep deficit (Zhengqing,et.al., 2017). Sleep disorders mainly reflected in the wakefulness activity and especially in cognition ability, such as learning and memory (Curcioetal., 2006; Lundetal., 2010). This is important problem in the student population. Students often complain about quality of sleep, sleep duration, efficiency, daytime sleepiness. All of this influence on the learning capacity, decreasing of ability of declaration and procedural processing of memory. Studies of the effects of sleep reduction or optimization have shown that neurocognitive and academic performance deteriorates and improves, respectively (Curcioetal., 2006). Evidences of the scientific researches have shown, that four basic neurological disorders, such as sleep disorders, emotional stress, depression and cognition disability are tightly correlatedphenomenon and study of the sleep disordersin this regard should be conducted in a complex manner.